Epidermal growth factor and remarkable correlations in a case series COVID-19 - Héctor José Pérez Hernández (Revista Cubana de Medicina Militar)
Introduction: Molecular links relate epidermal growth factor (EGF) to inflammatory phenomena. In the context of COVID-19, understanding the role of serum concentrations of EGF offered new possibilities for a better understanding of physiopathology and therapeutics. Objective: To explore the behavior of serum EGF values in patients with COVID-19, as well as to determine possible significant correlations between EGF, and analytical and clinical parameters of interest. Methods: Cross-sectional observational analytical study, in a series of COVID-19 cases that included 15 patients attended between august-september 2021. Variables included: Age, sex, comorbidities, respiratory rate, heart rate, hospital stay, neutrophils, lymphocytes, neutrophil-lymphocyte index. Summary measures: Absolute frequency, percentage, and the arithmetic mean were used. The statistical significance of observable differences between groups was explored with the chi-square test or Welch's t test with a= 0.05. Results: Notable correlation observed are rEGF-age= -0.6211 (p= 0.0206) overall, with rEGF-age= 0.2998 (p= 0.4030) in critically ill patients and rEGF-age= -0.9607 (p= 0.0000) in patients with care report. In the case of correlation with neutrophils, this is observed in the case of the subset of critical patients (rEGF-PNN= -0.4471, p= 0.3524); in relation to respiratory rate and heart rate, remarkably strong correlations were observed in critically ill patients (rEGF-Rr= 0.8220, p= 0.1928; rEGF-Hr= -0.9285, p= 0.1207). Conclusions: There is a plausible relationship between serum EGF values and COVID-19, with notably strong correlations for clinical parameters in the context of serious illness.